Prediction of Postictal Delirium Following Status Epilepticus in the ICU: First Insights of an Observational Cohort Study. Issue 12 (13th July 2021) - Baumann, Sira M.; Semmlack, Saskia; Hunziker, Sabina; Kaplan, Peter W.; De Marchis, Gian Marco; Rüegg, Stephan; Marsch, Stephan; Sutter, Raoul
Abstract : OBJECTIVES: To identify early predictors of postictal delirium in adult patients after termination of status epilepticus. DESIGN: Retrospective study. SETTING: ICUs at a Swiss tertiary academic medical center. PATIENTS: Status epilepticus patients treated on the ICUs for longer than 24 hours from 2012 to 2018. INTERVENTIONS: None. METHODS: Primary outcome was postictal delirium during post-status epilepticus treatment defined as an Intensive Care Delirium Screening Checklist greater than or equal to 4. Associations with postictal delirium were secondary outcomes. A time-dependent multivariable Cox proportional hazards model was used to identify risks of postictal delirium. It included variables that differed between patients with and without delirium and established risk factors for delirium (age, sex, number of inserted catheters, illness severity [quantified by the Sequential Organ Failure Assessment and Status Epilepticus Severity Score], neurodegenerative disease, dementia, alcohol/drug consumption, infections, coma during status epilepticus, dose of benzodiazepines, anesthetics, and mechanical ventilation). MEASUREMENTS AND MAIN RESULTS: Among 224 patients, post-status epilepticus Intensive Care Delirium Screening Checklist was increased in 83% with delirium emerging in 55% with a median duration of 2 days (interquartile range 1–3 d). Among all variables, only the history of alcohol and/or drug consumption was associated with increased hazards for delirium in multivariable analyses (hazard ratio = 3.35; 95% CI, 1.53–7.33). CONCLUSIONS: Our study provides first exploratory insights into the risks of postictal delirium in adult status epilepticus patients treated in the ICU. Delirium following status epilepticus is frequent, lasting mostly 2–3 days. Our findings that with the exception of a history of alcohol and/or drug consumption, other risk factors of delirium were not found to be associated with a risk of postictal delirium may be related to the limited sample size and the exploratory nature of our study. Further investigations are needed to investigate the role of established risk factors in other status epilepticus cohorts. In the meantime, our results indicate that the risk of delirium should be especially considered in patients with a history of alcohol and/or drug consumption.